2020
DOI: 10.1080/09546553.2020.1718661
|View full text |Cite
|
Sign up to set email alerts
|

Disaggregating Lone-actor Grievance-fuelled Violence: Comparing Lone-actor Terrorists and Mass Murderers

Abstract: and Crime Science. Her research focusses on detecting dynamic patterns across a spectrum of grievance-fuelled violence to enhance the threat assessment of these types of offenders. She works as a research assistant on the ERC-funded Grievance project (see below).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 43 publications
1
28
0
Order By: Relevance
“…Clemmow et al utilised cluster analysis to identify variables to distinguish between loneactor terrorists and mass murderers within a U.S. sample. 83 Although some differences were noted, including lone-actor terrorists being more likely to engage in leakage behaviours, much commonality was found across propensity factors, situational factors, preparatory indicators and network factors examined. For Europe, comparing lone-actor terrorists with 'ordinary' homicide offenders, Liem et al found lone actors to exhibit higher levels of education.…”
Section: Theme 4: Similarities With Other Lone Offender Typesmentioning
confidence: 99%
“…Clemmow et al utilised cluster analysis to identify variables to distinguish between loneactor terrorists and mass murderers within a U.S. sample. 83 Although some differences were noted, including lone-actor terrorists being more likely to engage in leakage behaviours, much commonality was found across propensity factors, situational factors, preparatory indicators and network factors examined. For Europe, comparing lone-actor terrorists with 'ordinary' homicide offenders, Liem et al found lone actors to exhibit higher levels of education.…”
Section: Theme 4: Similarities With Other Lone Offender Typesmentioning
confidence: 99%
“…Many of the considerations in the present work are not confined to terrorism, but can be extended to other forms of grievance-based offending. Evidence on the online radicalization process does not, generally speaking, presuppose any specifics in the domain of terrorism, and findings on information leakage and general offender characteristics are, as pointed out in the beginning, very similar across different forms of grievance-fueled violence (Capellan, 2015;Kenyon et al, 2021a;Clemmow et al, 2022). There is still, however, careful scrutiny required since terrorist offending can comprise much more than immediate acts of violence.…”
Section: Current Limitations and Outlookmentioning
confidence: 98%
“…Online radicalization processes have been of major concern, not only in the area of terrorism, but in the wider field of grievance-based violence. In fact, recent work has introduced a comparative approach that builds on the commonalities between perpetrators of, for example, high school shootings, hate crimes, and terrorist attacks ( Brooks and Shaw, 2022 ; Clemmow et al, 2022 ; Ebbrecht, 2022 ). In particular for offenders deemed to be lone actors, the boundaries between terrorism and other forms of offending are blurred ( Capellan, 2015 ; Kenyon et al, 2021a ; Clemmow et al, 2022 ).…”
Section: Online Radicalization As a Cause For Common Concernmentioning
confidence: 99%
“…Specifically, we encourage readers to use observable behavioral indicators before the public mass shooting and during the incident to assign an intent rating score to each individual incident. Prior research has documented a wide variety of discrete public mass shooter behaviors and characteristics relevant to planning, preparation, and perpetration (Clemmow et al, 2022;Cowan & Cole, 2022;Fox & Levin, 1994;Newman et al, 2004;O'Toole, 2000), including bringing spare guns and ammunition, leakage, wearing a costume to invoke fear or mimic violent role models, aiming and firing at victims and witnesses, having a targeted or symbolic grievance against the location, stockpiling guns and ammunition, or training to shoot. Importantly, these indicators are readily observable to guardians and handlers (Felson, 1995) surrounding the perpetrator and to witnesses and survivors at the crime scene.…”
Section: An Empirical Strategy For Measuring Mass Intentmentioning
confidence: 99%